Penggunaan tepung ampas kelapa dan dedak padi dalam pakan untuk meningkatkan laju pertumbuhan dan kelangsungan hidup ikan bandeng (Chanos chanos) - Solo, Klemensius L; Tobuku, Ridwan; Tjendanawangi, Agnette (Nusa Cendana University, 2023)
This research has been carried out for 2 months at the Oesapa Beach Fish Seed Center (BBIP), aiming to determine the percentage of coconut pulp flour and rice bran in optimal feed formulations to increase the growth rate and survival of milkfish (Chanos chanos). The experiment used a completely randomized design (CRD) with 3 treatments and 3 replications. The treatments tested were treatment A (addition of 10% coconut dregs flour and 30% rice bran flour), treatment B (addition of 20% coconut dregs flour and 20% rice bran), treatment C (addition of 30% coconut dregs flour and 10% rice bran %) and control k1 (commercial pellets). The results showed that the best feed given in the form of coconut dregs flour and rice bran to milkfish was obtained in treatment B (20% coconut dregs flour and 20% rice bran), giving the highest absolute growth of 25.85 g, survival of 86.66% and FCR of 5.33%.